2014
DOI: 10.1007/s11033-014-3587-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis and molecular characterization of spontaneously outgrown human lymphoblastoid cell lines

Abstract: In vitro, the infection of human B-cells with the lymphotropic gammaherpesvirus Epstein-Barr virus (EBV) induces formation of permanently growing lymphoblastoid cell lines (LCL). In a spontaneously outgrown LCL (cell line CSIII), we detected nucleotide sequence variations of the EBV nuclear antigen 1 (EBNA1) RNA that was different from the reference sequence of EBNA1 in the prototypic EBV strain B95-8. In the present study, we molecularly and functionally characterized this virus isolate in comparison to LCL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In this regard our findings are in keeping with those of Burrows and colleagues [ 11 ], who demonstrated similar patterns of EBNA-1 sequence variation predominantly within the C-terminal region in both MS cases and controls, in a study that did involve primary B lymphocyte cultures. Both studies, as well as a more recent analysis of spontaneously outgrown human lymphoblastoid cell lines [ 65 ] are in agreement in demonstrating that the majority of autologous sequences do not align closely with the widely used B95-8 laboratory strain–a result that is perhaps not surprising given that this strain was originally identified following transfusion-associated EBV in an elderly woman and subsequently selected for its ability to efficiently immortalise B lymphocytes [ 66 ].…”
Section: Discussionmentioning
confidence: 55%
“…In this regard our findings are in keeping with those of Burrows and colleagues [ 11 ], who demonstrated similar patterns of EBNA-1 sequence variation predominantly within the C-terminal region in both MS cases and controls, in a study that did involve primary B lymphocyte cultures. Both studies, as well as a more recent analysis of spontaneously outgrown human lymphoblastoid cell lines [ 65 ] are in agreement in demonstrating that the majority of autologous sequences do not align closely with the widely used B95-8 laboratory strain–a result that is perhaps not surprising given that this strain was originally identified following transfusion-associated EBV in an elderly woman and subsequently selected for its ability to efficiently immortalise B lymphocytes [ 66 ].…”
Section: Discussionmentioning
confidence: 55%
“…RBMS1 has also been suggested to play a role in apoptosis, specifically RBMS1 inhibits cell proliferation by inducing apoptosis. Additionally, it can prevent the lytic cycle of viruses …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it can prevent the lytic cycle of viruses. 24,25 The three aforementioned genes all have the function of suppressing cell proliferation. We found that their levels were higher in DMSCs from patients with psoriasis than in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expense and complexity of obtaining sufficient dendritic cells due to low frequency in peripheral blood and in vitro proliferation capacity of dendritic cells has limited its wide application, particularly in critically ill cancer patients . Alternatively, Epstein–Barr virus (EBV)‐transformed B‐lymphoblastoid cell lines (LCLs) have been demonstrated to be excellent professional APCs and most importantly, LCLs could be easily obtained by culturing peripheral blood lymphocytes from EBV‐positive humans in vitro or by incubating with B95‐8 cell supernatant . However, neoantigen‐loaded LCLs could stimulate not only neoantigen‐specific T cells but also nonspecific T cells, which could be due to expression of both EBV antigens and endogenous nonsynonymous mutations arising in LCLs .…”
Section: Introductionmentioning
confidence: 99%
“…5 Alternatively, Epstein-Barr virus (EBV)-transformed Blymphoblastoid cell lines (LCLs) have been demonstrated to be excellent professional APCs and most importantly, LCLs could be easily obtained by culturing peripheral blood lymphocytes from EBV-positive humans in vitro or by incubating with B95-8 cell supernatant. [6][7][8][9][10] However, neoantigen-loaded LCLs could stimulate not only neoantigen-specific T cells but also nonspecific T cells, 1 which could be due to expression of both EBV antigens and endogenous nonsynonymous mutations arising in LCLs. [11][12][13] Therefore, although LCLs are commonly used as efficient APC to elicit T-cell responses, some concerns have been raised about their extensive use because of possible genetic changes during LCL generation, maintenance, and immortalization.…”
Section: Introductionmentioning
confidence: 99%